DAYA SAING PRODUK PERTANIAN DAN PERIKANAN INDONESIA DALAM PERSPEKTIF MANAJEMEN PRODUKTIVITAS DAN KUALITAS - Priangani, Ade; Iba, Zainuddin (JURNAL KEBANGSAAN, 2019)
This study discusses the concept, problematic, and the application of quality management to improve productivity. Specifically this study presents: a philosophical foundation, criteria and measuring tools, models and approach to quality management, as well as discuss the implementation and application in developing organizational management, empowerment (empowering) individuals within the organization, so it has a goal, a sense, initiative, and works to display the productive quality of performance excellence.Keywords: competitiveness, agriculture, fishery, productivity, quality